Implikasi Institutional Ownership Dalam Pengaruh Capital Intensity, Kompensasi Rugi Fiskal, Dan Tunneling Incentive Terhadap Tax Avoidance - Nadila Indah Ratnandari; Fatchan Achyani (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
This study aims to obtain empirical evidence of the effect of Capital Intensity, Fiscal Loss Compensation, and Tunneling Incentives on Tax Avoidance with Institutional Ownership as a moderating variable. This study uses a population of manufacturing companies in the consumption sector for the period 2019-2022. The sample determination was carried out with purposive sampling. The data analysis technique used is panel data Moderated Regression Analysis (MRA). The results showed that Capital Intensity has no effect on Tax Avoidance, Fiscal Loss Compensation, and Tunneling Incentive have a positive effect on Tax Avoidance, Institutional Ownership cannot moderate Capital Intensity on Tax Avoidance, and Institutional Ownership can moderate Fiscal Loss Compensation and Tunneling Incentive on Tax Avoidance.